2013
DOI: 10.1177/004005991304600207
|View full text |Cite
|
Sign up to set email alerts
|

Improving Vocational Skills of Students with Disabilities

Abstract: Covert audio coaching involves a teacher, paraprofessional, job coach, supervisor, or another individual (henceforth referred to as coach) delivering immediate feedback to a person performing a skill via a two-way radio or walkie-talkie and an earbud speaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Dotto-Fojut and colleagues (2011) taught four participants how to request assistance for a workrelated problem while in an employment setting. Other targeted skills included T-shirt folding (Bennett et al 2013b), clerical skills (Bennett et al 2013a;Dotson et al 2013), shipping products (Burke et al 2013), newspaper route (Robinson and Smith 2010), cover letter writing (Pennington et al 2014), cleaning (Kellems and Morningstar 2012), recycling (Bennett 2013), stocking inventory (Kellems and Morningstar 2012), self-employment skills (Dotson et al 2013), and sorting mail (Alexander et al 2013). All reviewed studies reported that participants acquired the target skills to satisfactory levels of performance.…”
Section: Impact Studiesmentioning
confidence: 99%
“…Dotto-Fojut and colleagues (2011) taught four participants how to request assistance for a workrelated problem while in an employment setting. Other targeted skills included T-shirt folding (Bennett et al 2013b), clerical skills (Bennett et al 2013a;Dotson et al 2013), shipping products (Burke et al 2013), newspaper route (Robinson and Smith 2010), cover letter writing (Pennington et al 2014), cleaning (Kellems and Morningstar 2012), recycling (Bennett 2013), stocking inventory (Kellems and Morningstar 2012), self-employment skills (Dotson et al 2013), and sorting mail (Alexander et al 2013). All reviewed studies reported that participants acquired the target skills to satisfactory levels of performance.…”
Section: Impact Studiesmentioning
confidence: 99%
“…Skill teaching may be considered to be important in the education of individuals with special needs. In the studies on the field of special education, skill teaching is emphasized more than scholar skills such as reading and writing (Eliçin, 2015;Şengül, 2008), solving math problems (Karabulut, 2015;Kasap, 2015;Yakubova et al, 2015), overlapping professional (Bennett, 2013;Kwon and Lee, 2016;Özbey, 2015) and daily life skills (Kalaycı, 2014;Kaya, 2015;Kurtoğlu, 2015;Stanton-Chapman and Brown, 2015). Social leadership/enlightening category features the role of special education teachers in bringing individuals with special needs in society, eliminating conflicts between the society and these individuals, and promoting the profession within the society.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Graduating from high school and transitioning to adulthood is a time of heightened opportunities (Bennett, 2013) but also of new risks relating to "the individual, the family, and the social service system" (Blacher, 2001, p. 173). A historical piece by Halpern (1994) provided a comprehensive and frequently cited definition of transition for youth with ID: Transition refers to a change in status from behaving primarily as a student to assuming emergent adult roles in the community.…”
Section: Independent Daily Living For Young Adults With Idmentioning
confidence: 99%